The profession of teaching - Emrick, Victor (My University, 1895)
Introduction: As I think of my boyhood days some of my most distinct and pleasant recollections, are those days spent in school. Well do I remember the little country school-house with its dilapidated appearance without, and its gloomy walls within, of broken seats, torn maps, mischievous scholars, and especially the dull ones, and of the punishments inflicted; these are but a few of the many incidents that are remembered of those school days.
Citation: Emrick, Victor. The profession of teaching. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Boyhood; School; Teaching; Theses; Manuscripts (documents)